2002
DOI: 10.1038/sj.jhh.1001412
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipping in diabetic patients: insights from the siesta

Abstract: Non-dipping, ie failure to lower blood pressure during sleep, has been found to be more prevalent in diabetic than in non-diabetic subjects. However, the reasons remain to be clarified. Diabetic patients may wake up more frequently during the night (for instance, due to nocturia). This may result in inclusion of awake blood pressure measurements in the night-time average and thus erroneously raise this average, causing misclassification of patients as non-dippers. However, nondipping in diabetes may be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…It has been shown previously that the diurnal-nocturnal differences in blood pressure are smaller among T2DM patients than in controls. 18,19 A reduction in the actions of insulin may be one of the important physiological defects underlying the abnormal circadian rhythm of blood pressure in patients with T2DM and other related diseases. 20 Non-dipper hypertensive patients have been shown to be more insulin resistant and glucose intolerant than dipper hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that the diurnal-nocturnal differences in blood pressure are smaller among T2DM patients than in controls. 18,19 A reduction in the actions of insulin may be one of the important physiological defects underlying the abnormal circadian rhythm of blood pressure in patients with T2DM and other related diseases. 20 Non-dipper hypertensive patients have been shown to be more insulin resistant and glucose intolerant than dipper hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among subjects reporting having taken an uninterrupted afternoon siesta, diabetics displayed a similar naptime BP decline to their night-time BP decline, which was blunted as compared to the non-diabetic controls. 75 Several small studies have shown that insulin resistance in non-diabetic hypertensive subjects is also associated with a reduced nocturnal fall in BP. [76][77][78] Mancia et al, however, did not find an increase in non-dipping pattern in patients with the metabolic syndrome, although less than one-third of these individuals had impaired glucose intolerance.…”
Section: Clinical Conditionsmentioning
confidence: 99%
“…Despite the high frequency of non-dipping pattern in diabetes mellitus (DM) (Perk et al 2002) and its close relationship with IR (Della Mea et al 2005), the association of non-dipping pattern with MS surprisingly failed to be proven (Cuspidi et al 2004c). This might be due to the inadequacy of the diagnostic method of MS to reflect the excess risk contributed to this syndrome.…”
mentioning
confidence: 99%